Effect of Bioinsectiside Extract of Gynura procumbens L. Leaves For Control of Cabbage Copper Pests (Crocidolomia binotalis Zell.) - Safrida, Safrida; Yuliani, Wirda; Sapurti, Mimie; -, Supriatno; -, Abdullah (Kalwedo Sains (KASA), 2020)
Pest control efforts carried out by farmers in Indonesia still often use synthetic insecticides that can cause negative effects on the environment, human health, and increasing pest populations It is expected that the control of Cabbage Head Caterpillars (C. binotalis Zell.) using plant bioinsecticides Gynura procumbens L can minimize negative effects on the environment. The purpose of this study was to determine the effect of G. procumbens L leaf extract on the mortality of Cabbage Head Caterpillar (C. binotalis Zell.) And to know the Lethal Consentration (LC50) of Head Caterpillars (C. binotalis Zell.). The method used is an experimental method with a completely randomized design (CRD) consisting of 6 treatments and 4 replications. Toxicity tests on Cabbage Head caterpillars are performed on a laboratory scale. Data will be analyzed using Analysis of Variants (ANOVA) and then a follow-up test is the smallest significant difference test (LSD) and a probit regression analysis is performed. The addition of G. procumbens L leaf extract significantly affected (p <0.05) on cabbage head caterpillar mortality. The provision of of G. procumbens L leaf extract at a concentration of 5,000 ppm caused the death of caterpillar crop by 100%. The concentration of the extract that caused 50% (LC50) death of Cabbage Head Caterpillars (C. binotalis Zell.) Was 3,000 ppm